Classical Insights, Contemporary Relevance: Understanding Tafsīr bi-al-Maʾthūr in Qurʾānic Studies - Md. Mahdi Hasan; Choirul Ahmad; Md. Rafiqul Islam (Studia Quranika: Jurnal Studi Quran)
This paper explores tafsīr bi-al-maʾthūr, or tradition-based Qurʾānic exegesis, examining its core elements, interpretive diversity, and relevance in both historical and contemporary contexts. Defined by reliance on the Qurʾān itself, prophetic traditions, and the interpretations of the Companions and Successors, tafsīr bi-al-maʾthūr is foundational in Islamic scholarship for preserving original meanings of the Qurʾān. However, its dependence on early sources raises questions about its adaptability to current ethical, legal, and social issues within Muslim communities. Through a qualitative analysis, this study investigates primary interpretative methods within tafsīr bi-al-maʾthūr, including tafsīr al-Qurʾān bi-l-Qurʾān, tafsīr bi-l-ḥadīth, and interpretations by the Companions and Successors. The paper reveals how tafsīr bi-al-maʾthūr maintains Qurʾānic authenticity while offering insights into its potential relevance for contemporary applications. This study contributes to Qurʾānic studies by affirming tafsīr bi-al-maʾthūr as both a resilient and adaptable approach, balancing fidelity to foundational texts with interpretive flexibility in modern Islamic discourse.